Electrochemically exfoliated graphene as solution-processable, highly conductive electrodes for organic electronics - Parvez, Khaled; Li, Rongjin; Puniredd, Sreenivasa Reddy; Hernandez, Yenny; Hinkel, Felix; Wang, Suhao; Feng, Xinliang; Muellen, Klaus (ACS nano, 2013)
Solution-processable thin layer graphene is an intriguing nanomaterial with tremendous potential for electronic applications. In this work, we demonstrate that electrochemical exfoliation of graphite furnishes graphene sheets of high quality. The electrochemically exfoliated graphene (EG) contains a high yield (>80%) of one-to three-layer graphene flakes with high C/O ratio of 12.3 and low sheet resistance (4.8 kΩ/□ for a single EG sheet). Due to the solution processability of EG, a vacuum filtration method in association with dry transfer is introduced to produce large-area and highly conductive graphene films on various substrates. Moreover, we demonstrate that the patterned EG can serve as high-performance source/drain electrodes for organic field-effect transistors. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemical exfoliation; high-quality graphene; organic field-effect transistors; solution processing